Acute pain after breast surgery and reconstruction: A two‐institution study of surgical factors influencing short‐term pain outcomes. Issue 4 (20th June 2020) - Azad, Amee D.; Bozkurt, Selen; Wheeler, Amanda J.; Curtin, Catherine; Wagner, Todd H.; Hernandez‐Boussard, Tina
Abstract: Background and Objectives: Acute postoperative pain following surgery is known to be associated with chronic pain development and lower quality of life. We sought to analyze the relationship between differing breast cancer excisional procedures, reconstruction, and short‐term pain outcomes. Methods: Women undergoing breast cancer excisional procedures with or without reconstruction at two systems: an academic hospital (AH) and Veterans Health Administration (VHA) were included. Average pain scores at the time of discharge and at 30‐day follow‐up were analyzed across demographic and clinical characteristics. Linear mixed effects modeling was used to assess the relationship between patient/clinical characteristics and interval pain scores with a random slope to account for differences in baseline pain. Results: Our study included 1402 patients at AH and 1435 at VHA, of which 426 AH and 165 patients with VHA underwent reconstruction. Pain scores improved over time and were found to be highest at discharge. Time at discharge, 30‐day follow‐up, and preoperative opioid use were the strongest predictors of high pain scores. Younger age and longer length of stay were independently associated with worse pain scores. Conclusions: Younger age, preoperative opioid use, and longer length of stay were associated with higher levels of postoperative pain across both sites.